2020
DOI: 10.1111/jpy.13015
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Invaders: The Case of Ceratium furcoides (Gonyaulacales, Dinophyceae) in South America

Abstract: Ceratium furcoides is an invasive freshwater dinoflagellate that in the last three decades has expanded its geographic distribution in South America, being recently found in Paraná River floodplain (Argentina). Despite growing concern about the presence and impacts of this invader, information regarding genetic diversity in the Southern Hemisphere is missing. This work constitutes the first phylogenetic characterization of Ceratium populations of South America, particularly, from the Paraná system. After taxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Invasive microbial species have mostly been studied in marine environments (Litchman 2010, Bailey 2015), while microbial freshwater invasions has been addressed lately (Pollingher 1988, Padisák 1997, Piccini et al 2011, Sassenhagen et al 2015, Roelke et al 2016). Ceratium furcoides (MBFG V) is an invasive species that recently began to expand from inland waters in the north of Brazil towards the south (Santos‐Wisniewski et al 2007, Boltovskoy et al 2013, Accattatis et al 2020). That expansion has been associated to C. furcoides ecological traits (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive microbial species have mostly been studied in marine environments (Litchman 2010, Bailey 2015), while microbial freshwater invasions has been addressed lately (Pollingher 1988, Padisák 1997, Piccini et al 2011, Sassenhagen et al 2015, Roelke et al 2016). Ceratium furcoides (MBFG V) is an invasive species that recently began to expand from inland waters in the north of Brazil towards the south (Santos‐Wisniewski et al 2007, Boltovskoy et al 2013, Accattatis et al 2020). That expansion has been associated to C. furcoides ecological traits (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In South America, the genus is considered invasive (Boltovskoy et al, 2013), the rst records having occurred in the 1990s ( Severiano et al, 2022). Its origin in the South American continent is still uncertain, although some researchers, such as Accattatis et al (2020), are trying to elucidate these points. The authors found that genetic sequences from South America have more similarity with the Asian and North American sequences than those from Europe, where it was rst reported (Levander, 1894).…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, C. furcoides se ha encontrado en cuerpos de agua continentales en Colombia (Bustamante Gil et al 2012), Brasil (Dias & Tucci 2020Severiano et al 2021;Lacerda Macêdo et al 2021), Bolivia (Morales 2016), Argentina (Zaburlín et al 2014Accattatis et al 2020) y Uruguay (Pacheco et al 2021), mostrando un patrón de colonización opuesta a C. hirundinella, es decir del norte al sur de Sudamérica.…”
Section: Introductionunclassified